1998
DOI: 10.1177/14034948980260010901
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in musculoskeletal-related long term sickness absence in Norway

Abstract: Long-term sickness absence due to musculoskeletal health problems was strongly associated with gender, age, income, and diagnosis. Multivariate analysis indicated that the large gender differences in sickness absence might be overstated due to lack of adjustment for income and income-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 19 publications
5
36
1
13
Order By: Relevance
“…19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs. 19 The present study confirmed findings of no sex difference in relation to the risk of transition from sickness absence to disability pension, 22,30,34 implying that the threshold for taking sick leave is not lower among women than men.…”
Section: Comparison With Existing Literaturesupporting
confidence: 85%
“…19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs. 19 The present study confirmed findings of no sex difference in relation to the risk of transition from sickness absence to disability pension, 22,30,34 implying that the threshold for taking sick leave is not lower among women than men.…”
Section: Comparison With Existing Literaturesupporting
confidence: 85%
“…However, prevalences of back symptoms have been reported to be higher for men in some studies (4,8). Similarly, gender differences have also been found for sickness absence due to musculoskeletal symptoms (9)(10)(11)(12).…”
mentioning
confidence: 94%
“…Høyere sykefravaer blant kvinner enn blant menn er et konsistent funn i forskjellige land og ulike tidsavsnitt (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). I Norge viser data fra NHO at den absolutte kjønnsforskjellen i fravaer var noe mindre på 1970-tallet enn senere (4), og data fra NAV på sykefravaersprosent på 2000-tallet viser en stabil kjønnsforskjell på knappe tre prosentpoeng (12).…”
Section: Innledningunclassified
“…Graviditet er en fysiologisk tilstand med økt vulnerabilitet, og det er solid dokumentasjon for at risikoen for sykefravaer er betraktelig økt blant gravide i arbeidslivet (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Det er også sosiale gradienter i sykefravaer (3,7,(25)(26)(27)(28)(29), og ulikheter i sosioøkonomisk posisjon mellom kjønnene kan også tenkes å forklare forskjeller i fravaer. Arbeidsmiljø og forhold i hjemmet kan vaere risikofaktorer som kan vaere ulikt fordelt mellom kjøn-nene og som dermed kan forklare kjønnsforskjeller i sykefravaeret.…”
Section: Innledningunclassified
See 1 more Smart Citation